2015
DOI: 10.1002/jcp.25118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dasatinib, Nilotinib, and Imatinib in the Treatment of Chronic Myeloid Leukemia

Abstract: To overcome the drug resistance phenomenon induced by Imatibib (IM), in clinical practice, are often used second generation of tyrosine kinase inhibitors as Nilotinib (NIL); a such potent inhibitor of the BCR/ABL kinase and Dasatinib (DAS), a inhibitor of BCR/ABL kinase, and inhibitor SrC family kinase. In this study we evaluated the in vivo effect of DAS, NIL, and IM on intracellular calcium concentration, oxidative stress, and apoptosis in peripheral blood leukocytes of 45 newly diagnosed patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Nilotinib is a selective BCR‐ABL tyrosine kinase inhibitor, while dasatinib is a multi‐targeted inhibitor of BCR‐ABL tyrosine kinase and SRC family kinases (Ciarcia et al , ; Marfe et al , ). There is also some evidence that dasatinib may inhibit the circadian clock kinase CK1 (Karaman et al , ), which may explain its period‐lengthening effects (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Nilotinib is a selective BCR‐ABL tyrosine kinase inhibitor, while dasatinib is a multi‐targeted inhibitor of BCR‐ABL tyrosine kinase and SRC family kinases (Ciarcia et al , ; Marfe et al , ). There is also some evidence that dasatinib may inhibit the circadian clock kinase CK1 (Karaman et al , ), which may explain its period‐lengthening effects (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…24,25) Dasatinib has a remarkably short half-life compared with those of other TKIs and the plasma concentration of dasatinib cannot be maintained for a long time. However, the therapeutic effect of dasatinib has been reported to be superior to those of other TKIs 20,26,27) Previous studies showed that dasatinib not only inhibited its therapeutic target BCR-ABL but also strongly inhibited other tyrosine kinases involved in cell proliferation such as SRC, whereas imatinib inhibited only BCR-ABL. 28,29) Thus, the mechanisms underlying the thera-peutic effects of imatinib and dasatinib are different.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tyrosine-kinase inhibitors (TKIs) has been well studied in the context of CML, with imatinib and dasatnib being examples. 37,38 On the other hand, data on the use of TKIs for treating CLL/ SLL is limited. 39,40 Veldurthy et al 41 demonstrated that CLL/SLL with parameters associated with unfavorable outcomes (IGVH unmutated, ZAP70, and CD38 expression) showed some response with dasatinib therapy.…”
Section: Discussionmentioning
confidence: 99%